Optical properties of colorectal muscle in visible/NIR range - Carneiro, Isa (2018)
Knowledge of the optical properties of tissues is necessary, since they change from tissue to tissue and can differ between normal and pathological conditions. These properties are used in light transport models with various areas of application. In general, tissues have significantly high scattering coefficient when compared to the absorption coeficiente and such difference usually increases with decreasing wavelength. The study of the wavelength dependence of the optical properties has been already made for several animal and human tissues, but extensive research is still needed in this field. Considering that most of the Biophotonics techniques used in research and clinical practice use visible to NIR light, we have estimated the optical properties of colorectal muscle (muscularis propria) between 400 and 1000 nm. The samples used were collected from patients undergoing resection surgery for colorectal carcinoma. The estimated scattering coefficient for colorectal muscle decreases exponentially with wavelength from 122 cm-1 at 400 nm to 95 cm-1 at 650 nm and to 91 cm-1 at 1000 nm. The absorption coefficient shows a wavelength dependence according to the behavior seen for other tissues, since it decreases from 8 cm-1 at 400 nm to 2.6 cm-1 at 650 nm and to 1.3 cm-1 at 1000 nm. The estimated optical properties differ from the ones that we have previously obtained for normal and pathological colorectal mucosa. The data obtained in this study covers an extended spectral range and it can be used for planning optical clearing treatments for some wavelengths of interest.